Workplace Whistleblower Protection in Poland: Current Situation and Perspectives - Skupień, Dagmara; Agnieszka Gralak (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
The chapter analyses the current legal situation of whistleblowers in work-related context in Poland. Protection of whistleblowers is not regulated by a single comprehensive legal act but may be granted on the basis of different pieces of legislation as well as according to the case law of the Supreme Court, which established the concept of ‘permissible criticism’ expressed by a worker. The level of whistleblower protection is by no means satisfactory, especially as regards atypical workers. The author assesses the shortcomings of the current legal situation and presents proposals for improvement in the light of the EU Whistleblower Protection Directive and international conventions ratified by Poland.